Theory financial accounting - Valix, Conrado; Valix, Christian Aris (Manila, Philippines : GIC Enterprises & Co., Inc., 2018)
This book serves as a reviewer in Financial Accounting in the Philippine CPA Licensure Examinations. This reviewer is largely based on the Conceptual Framework for Financial Reporting, Philippine Accounting Standards or PAS and Philippine Financial Reporting Standards of PFRS.
Chapter 1: The Accounting profession -- Chapter 2: Conceptual framework; assumptions and financial reporting -- Chapter 3: Conceptual framework; qualitative characteristics -- Chapter 4: Conceptual framework; elements of financial statements -- Chapter 5: Accounting process -- Chapter 6: Financial statements -- Chapter 7: Statement of financial position -- Chapter 8: Notes to financial statements -- Chapter 9: Related party disclosures -- Chapter 10: Events after the reporting period -- Chapter 11: Statement of comprehensive income -- Chapter 12: Statement of changes in equity; financial capital and physical capital -- Chapter 13: Noncurrent assets held for sale -- Chapter 14: Discontinued operations -- Chapter 15: Accounting estimate -- Chapter 16: Accounting policy; prior period error -- Chapter 17: Interim financial reporting -- Chapter 18: Operating segments -- Chapter 19: Cash and cash equivalents -- Chapter 20: Accounts receivable -- Chapter 21: Notes receivable -- Chapter 22; Receivable financing -- Chapter 23: Inventories -- Chapter 24: Inventory cost flow -- Chapter 25: Lower of cost and net realizable value -- Chapter 26: Gross profit and retail method -- Chapter 27: Biological assets -- Chapter 28: Financial instruments -- Chapter 29: Financial assets at fair value -- Chapter 30: Investment in associate -- Chapter 31: Financial asset at amortized cost ; fair value option -- Chapter 32: Investment property -- Chapter 33: Derivatives -- Chapter 34: Property, plant and equipment -- Chapter 35: Government grant -- Chapter 36: Borrowing costs -- Chapter 37: Land , building and machinery; capital and revenue expenditure -- Chapter 38: Depreciation -- Chapter 39: Depletion -- Chapter 40: Revaluation -- Chapter 41: Impairment of asset -- Chapter 42: Intangible assets -- Chapter 43: Specific intangible assets -- Chapter 44: Research and development cost -- Chapter 45: Liabilities; premium, warranty, and deferred revenue -- Chapter 46: Provision -- Chapter 47: Contingent liability and contingent asset -- Chapter 48: Bonds payable -- Chapter 49: Effective interest method -- Chapter 50: Compound financial instrument -- Chapter 51: Note payable; debt restructure -- Chapter 52: Lessee accounting -- Chapter 53: Lessor accounting -- Chapter 54: Accounting for income tax -- Chapter 55: Employee benefits -- Chapter 56: Shareholder's equity -- Chapter 57: Retained earnings -- Chapter 58: Share-based compensation -- Chapter 59: Book value per share -- Chapter 60: Earnings per share -- Chapter 61: Cash and accrual basis -- Chapter 62: Error correction -- Chapter 63: Statement of cash flows -- Chapter 64: Hyperinflation; current cost -- Chapter 65: Small and medium-sized entities -- Chapter 66: Small and medium-sized entities; multiple choice.
Includes SMEs
Keywords: ACCOUNTING; ACCOUNTING -- STUDY GUIDES